1998
DOI: 10.1074/jbc.273.6.3765
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of the Menkes Disease Protein Reveals Common Biochemical Mechanisms Among the Copper-transporting P-type ATPases

Abstract: Menkes disease is a fatal neurodegenerative disorder of childhood caused by the absence or dysfunction of a putative P-type ATPase encoded on the X chromosome. To elucidate the function of the Menkes disease protein, a plasmid containing the open reading frame of the human Menkes disease gene was constructed and used to transform a strain of Saccharomyces cerevisiae deficient in CCC2, the yeast Menkes/Wilson disease gene homologue. ccc2⌬ yeast are deficient in copper transport into the secretory pathway, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
96
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 36 publications
6
96
2
Order By: Relevance
“…The ability of MNKP and WNDP to transport copper has been demonstrated (8,(17)(18)(19) and recent studies from Voskoboinik et al (8,20) confirmed that copper transport by these proteins is ATP-dependent. Further characterization of MNKP indicated that this protein formed a phosphorylated intermediate in a manner similar to other P-type ATPases (8).…”
mentioning
confidence: 91%
“…The ability of MNKP and WNDP to transport copper has been demonstrated (8,(17)(18)(19) and recent studies from Voskoboinik et al (8,20) confirmed that copper transport by these proteins is ATP-dependent. Further characterization of MNKP indicated that this protein formed a phosphorylated intermediate in a manner similar to other P-type ATPases (8).…”
mentioning
confidence: 91%
“…These domains are responsible for the cooperative effect of copper on WND catalytic phosphorylation activity (28). In contrast to WND, yeast complementation studies on MNK indicate that the first four N-terminal domains are important for copper transport (29). It may be that the domains function differently in the two ATPases.…”
mentioning
confidence: 99%
“…CTR1 is absolutely required for dietary copper absorption and is essential for cellular copper uptake [1][2][3][4][5][6][7]. Cellular copper export is equally important and is dependent on ATP7A and ATP7B [8][9][10][11][12]. In contrast to other organisms, hardly any transcriptional regulation of genes primarily involved in copper homeostasis exists in mammalian cells [13], and it is commonly accepted that regulation of copper homeostasis occurs predominantly by posttranslational mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Structure-function relationship of copper-transporting P-type ATPases Cellular copper export is dependent on the expression of ATP7A or ATP7B [9,10,[14][15][16][17][18]. ATP7A and ATP7B have dual functions depending on the cellular copper status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation